Flame‐assisted flash sintering: A noncontact method to flash sinter coatings on conductive substrates. Issue 2 (20th September 2017) - Johnson, Stephen L.; Venugopal, Ganesh; Hunt, Andrew T.
Abstract: We present a novel and effective method for sintering ceramic coatings onto metallic substrates. This new technique, called Flame‐assisted flash sintering (FAFS), utilizes a flame as both a heating source and a conformal, current‐carrying top electrode to facilitate flash sintering. Using this method, Yttria‐stabilized Zirconia (8 mol% Y, 8YSZ) coatings are sintered onto stainless steel substrates to controlled degrees of porosity in rapid fashion. Flame‐assisted flash sintering utilizes a dynamic soft electrode for flash sintering and has commercial potential to sinter ceramic coatings on complex‐shaped substrates for a variety of applications including tribological or thermal protection coatings.